Kreatywność jako przedmiot badań edukacyjno-muzycznych = Creativy as a subject of research in music education - Kataryńczuk-Mania, Lidia; Kołodziejski, Maciej; Kisiel, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article contains theoretical and research considerations on musical creativity. It focuses on artistic activities in the areas of creative and reproductive creativity and perception, referring to selected systemic solutions in music education. It is emphasized that both teachers and pupils, active participants in the artistic and educational process, play an important and creative role in the course of music education. The authors show different research approaches and emphasize the urgent need to conduct research showing the true picture of the implementation of creative music education.
Keywords: ekspresja twórcza; ekspresja odtwórcza; kreatywność muzyczna; kształcenie muzyczne; creative expression; reproductive expression; musical creativity; music education